Combined Percutaneous Transrenal and Transfemoral Endovascular Recanalization and Angioplastic Reconstruction of a Disrupted Transplant Renal Artery Stent: A Novel Salvage Technique. Issue 4 (7th January 2017) - Carpenter, D. J.; Mohan, S.; Ratner, L. E.; Schlossberg, P.
Abstract : Renal artery stenosis is the most common vascular complication following renal transplantation. Percutaneous endovascular transluminal angioplasty with stenting is the treatment of choice for clinically significant renal artery stenosis. The authors present a case describing a novel combined transrenal parenchyma and transfemoral approach to repairing a disrupted transplant renal artery stent. The patient's allograft renal artery stenosis was initially managed via the standard percutaneous approach, but during follow‐up the stent became disrupted and crushed, causing partial occlusion of the renal artery. This was manifested by persistently elevated serum creatinine values, lower extremity edema, and four‐medication hypertension. After a failed traditional percutaneous transfemoral attempt, the authors were able to successfully access the renal arterial system via a combined transrenal and transfemoral approach, using an upper‐pole artery through the renal parenchyma. This transrenal approach used a 3 Fr system, allowing the authors to get a wire across the stent, which they were previously unable to do. With wire access, they performed a balloon angioplastic reconstruction to restore the stent's patency, resulting in a reduction in serum creatinine, lower extremity edema, and blood pressure. This technique avoided a potentially difficult reoperative repair without immediate complication and provides a method for vascular access to the renal arterial system in select patients. Abstract : Utilizing a novel endovascular salvage technique, Carpenter et al employ a combined percutaneous transkidney parenchyma and transfemoral approach to perform a recanalization and angioplastic reconstruction of a crushed transplant renal artery stent.